Extra-gonadal germ cell tumour – what about the testis! - Johann FK; Praveen S; Christopher CKH; Goh EH; Razman J; Zulkifli MZ (Department of Surgery, UKM Medical Centre, 2011)
Extra-gonadal germ cell tumours (EGGCT) are rare. Therefore further investigations of the testis is aimed at sourcing a possible primary origin of gonadal tumour. Over the years, various case series on EGGCT have been reported questioning its true nature as in a majority of them, a primary source is found in the testis, thus representing a metastatic gonadal tumour. The testis pathology could be either a true germ cell foci, an intra-tubular epithelial neoplasia or an area of fibrosis, indicating a „burnt out tumour‟. We report a 39-year-old male who underwent laparotomy and excision of a retroperitoneal tumour. Histopathological examination revealed retroperitoneal lymph node of mixed germ cell tumour origin. Clinical and ultrasound examination of bilateral testis was normal. The patient refused orchidectomy or a testicular biopsy. He underwent four cycles of bleomycin, cisplatin, and etoposide with no evidence of tumour recurrence on follow up and remains disease free after 12 months of diagnosis. A literature review of EGGCT, its relation and factors relating with future testicular tumour is presented.